INFLUENCE OF THERMOMECHANICAL PROCESSING IN A STREAM OF HIGH-SPEED WIRE MILL ON QUALITATIVE CHARACTERISTICS OF HIGH-CARBON ROLLED WIRE - V. A. Lutsenko; P. A. Bobkov; O. M. Kirilenko; V. I. Gritsaenko; O. V. Lutsenko (Литьë и металлургия, 2011)
It is shown that as a result of introduction in flow of the mill 150 of RUP «BMZ» of new configuration of finishing train of block construction with system of interblock control of semi-finished rolled products temperature the qualitative characteristics output production have been improved.